Options for Low Income Countries Effective and Efficient Use of Tax Incentives for Investment : A Report to the G-20 Development Working Group by the IMF, OECD, UN and World Bank - International Monetary Fund; OECD; United Nations; World Bank (World Bank, Washington, DC, 2015)
Experience shows that there is often ample room for more effective and efficient use of investment tax incentives in low-income countries. Tax incentives generally rank low in investment climate surveys in low-income countries, and there are many examples in which they are reported to be redundant, that is, investment will have been undertaken even without them. And their fiscal cost can be high, reducing opportunities for much-needed public spending on infrastructure, public services or social support, or requiring higher taxes on other activities. This paper responds to a request of the G20 Development Working Group for an exploration of options for low-income countries’ effective and efficient use of tax incentives for investment. To that end, it develops principles for the design and governance of tax incentives and provides guidance on good practices in these areas. Since much of the pressure to offer incentives stems from an awareness of those offered by other countries, the paper also discusses options for international coordination to address the risk of mutually damaging spillovers from such tax competition. Finally, a separate background document develops practical tools and models that can help assess the costs and benefits of tax incentives, which is essential for informed decision making. The aim is thus to assist low-income countries (LICs) in reviewing and reforming their tax incentives, so as to better align them with their developmental objectives. This paper relates to other global initiatives aimed at strengthening domestic revenue mobilization in LICs.